Management of large or giant Extracranial carotid artery aneurysms: a single-center experience - AXiMuJiang AXiEr; Mirzat Turhon; Aierpati Maimaiti; Dilmurat Gheyret; Shihao Jiang; Kaheerman Kadeer; Riqing Su; Nizamidingjiang Rexiati; Kai Wang; Xiaojiang Cheng; Zengliang Wang; Maimaitili Aisha (BMC Neurology)
Abstract Background Extracranial carotid artery aneurysm (ECCA) is an infrequent disease with an incidence of less than 1%. However, our understanding is still incomplete, and the preferred method to treat ECAA remains unknown. Methods To share our initial experience with treatment options for large ECCAs. We have retrospectively included 15 patients who underwent treatment at our institution from 2015 to 2022. The treatment modality, patient demography, aneurysm morphology, and clinical and radiographic follow-data were collected and analyzed in all patients. Results During the study period, 15 patients (with 19 ECCAs) were diagnosed and treated, of whom 8 (53.3%) were male. The average age of the patients was 53.6 years. The primary presenting symptoms was pulsatile neck mass (10/15, 66.7%). The etiology of ECAAs included atherosclerotic (6/15, 40.0%), infectious (3/15, 20.0%), and dissecting (1/15, 6.7%), and iatrogenic due to acupuncture (1/15, 6.7%). The mean ± SD maximal diameter of the aneurysms was 23.8 ± 14.1 mm, with more than half of patients having aneurysms larger than 25 mm (52.6%). 79.0% aneurysm had intraluminal thrombus at admission. Six patients underwent successful neurosurgical resection for a total of seven ECCAs. Five patients received endovascular interventional treatment. The remaining four patients who presented with seven ECCAs were placed under observation. The mean follow-up period was 28.1 months. Out of the patients who received treatment, it was discovered that 10 of them had completely occluded at the latest imaging study. During the course of conservative observation, it was observed that in one patient, the aneurysm disappeared and the parent vessel became thinner following anti-infection treatment. Out of all the patients, only one who was treated with Willis stent experienced a large area of cerebral infarction after treatment, which ultimately resulted in their death. Conclusions ECCA is rare and mostly present with mass effect. Neurosurgical treatment was more frequently feasible in large ECCAs, and endovascular surgery was the first choice for pseudoaneurysms and dissecting aneurysms. Anti-inflammation treatment was available for some infectious cases.